PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KUALITAS PENGUNGKAPAN SUSTAINABILITY REPORT (Studi Empiris Pada Seluruh Perusahaan Yang Listing Di Bursa Efek Indonesia Periode 2011-2016) - Margaretha Barung; Aaron M. A. Simanjuntak; Linda Y. Hutadjulu (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
This study aims to obtain empirical evidence on the analysis of factors affecting the extent to which disclosure of sustainability reports are voluntary to companies in Indonesia. Factors used include the sizeof the Board of Commissioners, the proportion of Independent Commissioners, the size of the Audit Committee, Institutional Share Ownership, Concentrated Shares and Size of the Company. Measurement of sustainability report disclosure rates using Global Reporting Initiative (GRI). There are 91 items to detect the level of sustainability report disclosure. The population of this study is all financial data of companies listed on the BEI period 2011-2016. Sampling method used in this research is purposive sampling method. The samples used in this study are all companies that publish annual and financial reports during the period of observation. The total sample used in this study are 16 companies. The data used is secondary data from IDX. The analysis technique used is multiple linear regression analysis. The results of this study indicate that commissionaries independent, concentration institutional ownership and firm size have an effect on sustainability report disclosure, while board commisioner’s size, audit committee size and institutional capital ownership have no effect on sustainability report disclosure